Urgensi Pendekatan Ta‘līl al-Aḥkām dalam Reformasi Hukum Pidana Islam Kontemporer - Efendi, Zulfan (Jurnal El-Thawalib, 2025)
The urgency of discussing ta‘līl al-aḥkām in the development of modern Islamic criminal law also arises from the need to build legal legitimacy that can be intellectually justified. The objective is to examine how the concept of ta‘līl can be used to reformulate Islamic criminal law to be more adaptive to contemporary societal dynamics without compromising its normative essence. This research is qualitative in nature, employing a descriptive-analytical approach. The data sources in this study consist of secondary data obtained from classical and contemporary books and scriptures. Data collection techniques involve documentation, namely collecting, recording, and examining written materials relevant to the research topic. Meanwhile, the data analysis technique used is content analysis, which includes interpretation, classification, and synthesis of the collected data to find the relevance of the ta‘līl al-aḥkām concept to efforts in reconstructing Islamic criminal law in a contemporary context. This approach allows the researcher to identify the historical development of the concept of ta‘līl, the position of ‘illat (legal cause) in the construction of legal rulings, and its implications for the reform of Islamic criminal law. The results of this study indicate that ta‘līl al-aḥkām holds significant potential as a methodological tool to rationalize Islamic criminal law. Although there are criticisms of this approach, such as the risk of subjectivity and distortion of legal meanings, ta‘līl remains relevant for creating a just, contextual, and universally compatible criminal law system. With proper application and rigorous methodological oversight, ta‘līl can serve as a bridge between the Islamic legal tradition and the demands of modernity